2013
DOI: 10.1016/j.cell.2013.05.001
|View full text |Cite|
|
Sign up to set email alerts
|

Induction of Pluripotency in Mouse Somatic Cells with Lineage Specifiers

Abstract: SUMMARY The reprogramming factors that induce pluripotency have been identified primarily from embryonic stem cell (ESC)-enriched, pluripotency-associated factors. Here we report that during mouse somatic cell reprogramming, pluripotency can be induced with lineage specifiers that are pluripotency rivals to suppress ESC identity, most of which are not enriched in ESCs. We found that OCT4 and SOX2, the core regulators of pluripotency, can be replaced by lineage specifiers that are involved in mesendodermal (ME)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
246
1
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(270 citation statements)
references
References 84 publications
18
246
1
2
Order By: Relevance
“…This effect may be further strengthened by the proper addition of compounds that regulate key signal pathways or epigenetic modulators. On the other hand, exogenous pluripotency factors themselves may also act as lineage specifiers during the early stages of the reprogramming process, because it has been recently suggested that exogenous pluripotency factors may act as lineage specifiers during reprogramming to pluripotency (Shu et al, 2013). Furthermore, the overexpression of Review pluripotency factors in embryonic stem cells (ESCs) has been shown to induce differentiation (Loh and Lim, 2011).…”
Section: Pluripotency Factors For Indirect Lineage Reprogrammingmentioning
confidence: 98%
“…This effect may be further strengthened by the proper addition of compounds that regulate key signal pathways or epigenetic modulators. On the other hand, exogenous pluripotency factors themselves may also act as lineage specifiers during the early stages of the reprogramming process, because it has been recently suggested that exogenous pluripotency factors may act as lineage specifiers during reprogramming to pluripotency (Shu et al, 2013). Furthermore, the overexpression of Review pluripotency factors in embryonic stem cells (ESCs) has been shown to induce differentiation (Loh and Lim, 2011).…”
Section: Pluripotency Factors For Indirect Lineage Reprogrammingmentioning
confidence: 98%
“…According to this model, the balanced expression of Oct4 and Sox2 mutually activate each other for maintaining the pluripotent state. Interestingly, pluripotency can be achieved by simultaneous upregulation of Oct4 and Sox2 or other lineage specifiers that are involved in mesendodermal and ectodermal specification 90, 91. On the other hand, deviation from this balanced equilibrium induces differentiation into mesodermal or ectodermal cell types.…”
Section: Specific Gene Regulatory Network Circuits Regulate the Balanmentioning
confidence: 99%
“…Molecular heterogeneity and stochasticity of gene expression may drive a continuum of cancer cell states co-expressing stem cells and lineage-specific genes to encourage a greater likelihood of entering a CSC-like state, which may counterintuitively occur in response to the equilibrium between differentiation potentials. [42][43][44] Yamanaka stem cell technology for the recovery or foreseeing the evolutionary trajectory of individual cancers…”
Section: Understanding Cancer As a Disease Of Reprogramming And Diffementioning
confidence: 99%